Chemical and functional characterization of kañiwa (Chenopodium pallidicaule) grain, extrudate and bran - Repo-Carrasco-Valencia R. (2009)
Financial support from CONCYTEC (Concejo Nacional de Ciencia, Tecnología e Innovacion Tecnologica) is gratefully acknowledged. We thank Dr. Seppo Salminen for his critical reading and helpful comments on the manuscript.